Investigating the Strategic Interactions Among Gartnerâ€™s Eight Building Blocks of Successful Customer Relationship Management - Das, Subhasish; Mohapatra, Amiya Kumar; Mohanty, Debasis; Chaturvedi, Sharad (Indian Journal of Marketing, 2023)
Purpose : The present study intended to validate Gartnerâ€™s competency model (2001) in a real-world business scenario and to explore the strategic interactions among Gartnerâ€™s eight building blocks of successful customer relationship management (CRM). Methodology : Based on the theory of the CRM maturity model (CRM3), Gartnerâ€™s competency model, and the existing literature, the study identified the eight characteristics/building blocks, namely CRM vision, CRM strategy, CRM information, CRM technology, valued customer experience, organizational collaboration, CRM process, and CRM metrics. The survey method was used to collect the data through a well-validated questionnaire from the employees of the select organized retail stores located in Bhubaneswar, Odisha. The responses of 174 employees were considered for the analysis, and confirmatory factor analysis and structural equation modeling were used to analyze the interactions among the eight building blocks of CRM and to test the hypotheses. Findings : The results indicated the mediation of CRM information, valued customer experience, CRM technology, and organizational collaboration between CRM vision, CRM strategy, and CRM metrics. It also comprehensively explained how to implement the competency model proposed by Gartner. The study concluded that CRM can be best implemented in four phases: in phase one, firms must set CRM vision and strategy; in phase two, CRM information and technology; in phase three, valued customer experience, process, and organizational collaboration; and finally, CRM metrics. Implications : This study aimed to bridge the gap in the literature by analyzing the relationships between Gartnerâ€™s eight CRM components and providing an explanation of â€œhow and whyâ€ they interact. Additionally, it provided professionals and managers with appropriate methodologies and frameworks for the successful deployment of CRM. Originality : This study stands out since it is the first of its type to validate Gartnerâ€™s competency model in a real-world business environment. Additionally, it looked into how these elements interact with one another and offered the augmented CRM framework for effective implementation.